2016
DOI: 10.1016/j.ijsolstr.2016.03.019
|View full text |Cite
|
Sign up to set email alerts
|

The effect of initial stress on the propagation of surface waves in a layered half-space

Abstract: In this paper the propagation of small amplitude surface waves guided by a layer with a finite thickness on an incompressible half-space is studied. The layer and half-space are both assumed to be initially stressed. The combined effect of initial stress and finite deformation on the speed of Rayleigh waves is analyzed and illustrated graphically. With a suitable simple choice of constitutive law that includes initial stress, it is shown that in many cases, as is to be expected, the effect of a finite deformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…The dispersion relation is generally sensitive to the BCs, geometrical parameters and pre-stresses in the soft tissues [100,117119,127,128], which should be addressed during the development of a robust inverse method.…”
Section: Ultrasound-based Elastography Methodsmentioning
confidence: 99%
“…The dispersion relation is generally sensitive to the BCs, geometrical parameters and pre-stresses in the soft tissues [100,117119,127,128], which should be addressed during the development of a robust inverse method.…”
Section: Ultrasound-based Elastography Methodsmentioning
confidence: 99%
“…However, these papers dealing with bulging did not include residual stresses which are the main focus of this chapter. The same residual stress formulation exists in [95] and [99] and in the context of helical buckling bifurcation analysis due to torsion in [128].…”
Section: Introductionmentioning
confidence: 93%
“…Sham [15] investigated propagation of wave under the initial stress at the boundary between a layer and a half-space. Nam et al [16] showed the impact of initial stress in the layered half-space on the propagation of surface waves. Ejaz and Shams [17] analyzed the initial stress in compressible elastic materials on the wave propagation.…”
Section: Introductionmentioning
confidence: 99%